The effect of entrepreneurial orientation on export performance: Evidence from manufacturing SMEs in Tanzania - Denis Samwel Ringo; Amani Tegambwage; Isaac Kazungu (Cogent Business & Management, 2022)
AbstractThis paper examines the effect of innovativeness and proactiveness on export performance and the moderating effect of risk-taking on the relationship between innovativeness, proactiveness, and export performance. A quantitative research approach and a cross-sectional survey design were employed. In addition, stratified random sampling was employed to obtain data from 250 managers of manufacturing-exporting SMEs. Hypotheses were examined using the PROCESS macro test. The findings affirm that innovativeness is a significant predictor of export performance (β = 0.3854 and p < 0.001). However, negative effect of proactiveness on export performance was revealed (β = −0.1748 and p < 0.001). Risk-taking was found to be a significant moderator of the relationships between innovativeness and export performance (β = 0.2234 and p = 0.0009) as well as proactiveness and export performance (β = 0.1041 and p = 0.0271).The findings of this study broaden the applicability of RBV theory to an exporting context by examining the process through which entrepreneurial-orientation (EO) as an intangible resource leads to successful export performance. This study also contributes to the debate on the EO-export performance relationship by establishing the interplay effect between EO dimensions in enhancing export performance. The study contributes that risk-taking significantly moderates the relationship between innovativeness, proactiveness and export performance. Furthermore, the study recommends that the owners-managers of exporting SMEs develop and implement more innovative strategies, respond quickly to seize available export market opportunities, cultivate a positive attitude toward risks, and increase their capacity to take risks in order to improve their export performance.